Sisters outside: radical activists working for women prisoners - Lawston, Jodie Michelle (SUNY series in women, crime, criminology, 2009)
Introduction: Struggling for credibility -- Ideological origins of Women for Women Prisoners : from reform to revolution -- Negotiating racial privilege : (re) framing feelings of illegitimacy -- We're all sisters : bridging the gap between activists and prisoners -- Reconceptualizing prison and prisoners : attempts to resist get tough on crime discourse -- Conclusion: Contributions and reflections